2020
DOI: 10.1177/0306624x20936202
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Justice in China: Victim–Offender Mediation as the “Different Voice” of Female Judges

Abstract: Attempts to uncover the “different voice” of female judges through testing the statistical significance of judges’ gender in decision making have offered inconsistent results. Meanwhile, a proliferation of research suggests that such “voice” might be detected through qualitative analysis. Existing findings indicate that when female judges have discretionary power regarding case management, they will typically foster a process of settlement. Based on this information, I conducted eight months of fieldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The difference between the two theories is the use of prediction, which the realists contend is an integral element in the judicial decision-making process. The realists play an integral role in creating a distinction between decision-making and justification as they established a division between written judgments and judicial opinions and the actual process of making the ruling (Wei, 2021). They contend that judges use the facts and formal judicial rules to justify their choices, which means that formalists avoid the conclusion that judges make decisions based on their personal preference, personality, or hunch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the two theories is the use of prediction, which the realists contend is an integral element in the judicial decision-making process. The realists play an integral role in creating a distinction between decision-making and justification as they established a division between written judgments and judicial opinions and the actual process of making the ruling (Wei, 2021). They contend that judges use the facts and formal judicial rules to justify their choices, which means that formalists avoid the conclusion that judges make decisions based on their personal preference, personality, or hunch.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the first and the last ruling, the study found that favorable outcome drops by 60%. According to the research, the likelihood of a good result decreases from 60% in a first option to zero in a last one (Wei, 2021). As such, the theory established that the judges are influenced by extraneous factors, which they speculate was attributable to depletion of mental cognition.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Gender might also play a role, with some scholars arguing that women’s rationality is more oriented toward an ethic of care than men’s (Gilligan, 1982). Moreover, both women and minorities are more likely to refract their own experiences through the process, and are therefore more sensitive to specific offenses, such as sexual offenses against women (Wei, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%